Concept of project selection and its formalization in the absence of complete information - Rudenko, Sergey; Andrievska, Vera (Eastern-European Journal of Enterprise Technologies, 2016)
The basic object of the proposed approach is the “project map”, which is a set of project characteristics that are important for decision-making on the project selection in a particular situation. The “project map” is formed of the following blocks of project characteristics: enterprise objectives, cost-effectiveness, resources, risks, project potential, value, time. Each block contains a list of characteristics, typical examples of which are presented in the paper and can be extended. In particular, integrated project estimates, developed by modern researchers are shown in the “value” block. The conceptual model of the “project map – criteria – restrictions” system, which can serve as a universal basis for the formalization of the decision-making processes on the project selection under various conditions of information provision, taking into account possible modules of project characteristics is developed. Under this concept, the “project map” structure is reflected in the sets of restrictions and criteria for the selection procedure. This approach is versatile and allows forming the basis for subsequent selection considering project specifics and requirements. According to this model, the project selection procedure is formalized based on the possibility theory. The proposed approach involves “filtering” of projects using the confidence levels specified for the considered conditions, which reduces the volume of the operated information at subsequent stages. Also, in the framework of a unified scheme, the options of the project selection by one or more criteria are coordinated.